Avaliação econômica do cultivo do camarão marinho (Litopenaeus vannamei) em sistemas de cultivo superintensivo bifásico - Pereira Júnior, Vilson Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
Brazil has great potential for aquaculture, exalting mainly its natural conditions and favorable climate, and currently the producers seek alternative options for an economic activity that does not need large areas of land and that provides good productivity, where shrimp farming comes becoming a profitable activity option, and this one has stood out quickly and insightfully motivating several ventures. The objective of this work was to evaluate the economic viability of the implantation and operation of structures for the cultivation of marine shrimp in biphasic superintensive system in the city of Mossoró, Rio Grande do Norte, Brazil. This study was carried out in a shrimp farming company under construction with a biphasic superintensive cultivation system, located at Chafariz Site in the municipality of Mossoró / RN. For this, the monitoring and evaluation of the entire implementation process of the project was carried out, that is, from the project preparation stage and the environmental license withdrawal until the final stage of the coating and cover of the greenhouse type nurseries. A total of R$ 7,000.00 was spent in hiring a professional to withdraw the environmental license and prepare the project. For the implementation of this project, a total amount of R$ 464,936.15 was invested, all equipment, inputs and services being included in this amount, but certain structures such as support house, shed and etc. are not included in this amount. because they already exist on the spot. Thus, a cost per area of R$ 103.32.m2 was generated, with the highest percentages of this cost related to the coating and covering of greenhouse type greenhouses. In the production simulation of the farm, 8 cycles per year were developed, with a stocking density of 200 shrimp/m², the final individual average weight being 8g, with a survival of 75% generating a production per ha/cycle of 12,000 kg, and a production per year of 43,200 kg. For these results, there will be a total operating cost of R$ 410,895.00, thus generating a cost per kg of shrimp produced of R$ 9.51. Due to the gross revenue of R$ 766,900.00, a profit of R$ 345,105.00 will be obtained, generating a period of capital return of 1.35 years.
Monografia
Keywords: Camarão; Superintensivo; Produção; Investimento; Custo de produção; Investment; Superintensive; Shrimp; Production cost; Production; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA